Análisis de las vulnerabilidades de las redes inalámbricas del GAD Municipal del cantón Vinces - Felix Fajardo, Jacinto Johan (2021)
At present, Wireless networks are one of the most used means of connection to access the Internet and have good communication with other devices. For this reason, people seek to incorporate computer equipment in their work environment such as routers, which allow to maintain communication for the most part stable through Wi-Fi signals, this allows users to be connected to each other through a network with internet access. This causes people to want to access said networks improperly, to see the information that natural persons or workers provide when accessing web pages that request this information. The development of this project will have a qualitative research line and field research that will use the interview as a technique or research instrument, in order to gain knowledge about the current situation of wireless networks and in turn identify the threats and vulnerabilities that affect the network. The objective of the research is to carry out an analysis of the existing vulnerabilities in the different wireless networks, in order to help and provide information or Resources to information technology professionals to improve security in the wireless networks that the GAD has. Municipal.